Influence of the IL17A locus in giant cell arteritis susceptibility. Issue 9 (11th June 2014) - Márquez, A; Hernández-Rodríguez, J; Cid, M C; Solans, R; Castañeda, S; Fernández-Contreras, M E; Ramentol, M; Morado, I C; Narváez, J; Gómez-Vaquero, C; Martínez-Taboada, V M; Ortego-Centeno, N; et al.
Abstract : Objective: Different lines of evidence have highlighted the role of IL-17A in the inflammatory process occurring in giant cell arteritis (GCA). The aim of the present study was to assess whether the IL17A locus influences GCA susceptibility and its clinical subphenotypes. Methods: We carried out a large meta-analysis including a total of 1266 biopsy-proven GCA patients and 3779 healthy controls from four European populations (Spain, Italy, Germany and Norway). Five IL17A polymorphisms (rs4711998, rs8193036, rs3819024, rs2275913 and rs7747909) were selected by tagging and genotyped using TaqMan assays. Allelic combination and dependency tests were also performed. Results: In the pooled analysis, two of the five analysed polymorphisms showed evidence of association with GCA (rs2275913: PMH =1.85E−03, OR=1.17 (1.06–1.29); rs7747909: PMH =8.49E–03, OR=1.15 (1.04–1.27)). A clear trend of association was also found for the rs4711998 variant (PMH =0.059, OR=1.11 (1.00–1.23)). An independent effect of rs2275913 and rs4711998 was evident by conditional regression analysis. In addition, the haplotype harbouring the risk alleles better explained the observed association than the polymorphisms independently (likelihood p value <10 −05 ). Conclusions: Polymorphisms within the IL17A locus show a novel association with GCA. This finding supports the relevant role of the Th17 cells in this vasculitis pathophysiology.